The Role of Digital Twins and Estimating their Impact on the Field of Agriculture in Promoting Sustainability - C P, Shirley; Benny, Brijit; K, Vidhya; Jingle I, Berin Jeba (2024 4th International Conference on Pervasive Computing and Social Networking (ICPCSN), 2024)
Agriculture is the activity of cultivating natural resources that humans utilize for survival and economic benefit. It has evolved into one of the most significant industries in the day-to-day existence of all living organisms, providing access to food, a means of subsistence, etc. In reality, a country's agricultural output may have a direct or indirect impact on its food security and overall health. Despite the widespread adoption of these agricultural methods, various obstacles, including soil fertility and climate, can negatively impact the development and output of agricultural goods. As every living thing on Earth depends on agriculture for its existence, there is a constant need to find ways to overcome the problems faced. It is a well-acknowledged reality that contemporary issues demand modern solutions. Thus, it is critical to use developing technology to tackle the challenges that exist. The quality of life has been greatly enhanced by modern technologies. This concept has led to the introduction of several contemporary inventions and technologies that enhance the standard of life and advance the welfare of every individual. The demand for new technologies has been growing over time, and one promising technology with the potential to improve living standards and address long-standing issues in the agricultural sector is digital twin technology. It has made it possible to reduce labor and energy waste, among other things. Examining how digital twins might improve agricultural productivity and promote sustainability is part of the process of understanding digital twins and their place in the agricultural industry. The prerequisites and implementation strategies for encouraging the use of digital twins are covered. Since this is a new technology, a careful analysis of its benefits and limitations is necessary to properly address identified issues.